FDA Drug Quality Assurance Inspections: Frequency, Outcomes, and Time to Reinspection, 2008–2025 - Yunxiang Sun; Jeromie Ballreich; Joy Acha; Riya Modi; Mohammad Ali Alamdar Yazdi; Maqbool Dada; Tinglong Dai; Gerard Anderson; Mariana P Socal (Health Affairs Scholar, 2026)
Abstract Background FDA inspections are central to oversight of the pharmaceutical manufacturing base, but long-term inspection and reinspection patterns remain incompletely characterized. Methods We analyzed 25,629 FDA Drug Quality Assurance inspections conducted from October 2008 through December 2025. We described annual, regional, and outcome patterns. Linking inspections to facilities, we examined time to reinspection according to the outcome of preceding inspections. Results Annual Drug Quality Assurance inspections declined from 1,594 in 2019 to 461 in 2020 and increased to 1,218 in 2025. The United States remained the largest single region of inspection activity, but its contribution declined over time. The proportion of favorable inspection outcomes (no action indicated – NAI) decreased from 40.0% before the pandemic to 19.3% during and 23.7% after. Unfavorable outcomes (voluntary action indicated – VAI – and official action indicated – OAI) increased accordingly. The mean reinspection interval was 3.18 years after NAI, 2.96 after VAI, and 2.12 after OAI (P < .001). Median times were 4.08, 3.51, and 3.02 years, respectively. Conclusions FDA inspection activity had not returned to prepandemic levels by 2025. Unfavorable inspection outcomes were associated with earlier reinspection, consistent with risk-responsive oversight. However, the available data cannot establish whether follow-up was timely or adequate.